Systematic Review of Determinants of Organizational Performance of Craft SMEs in the Era of Industry 4.0: The Mediation Role of Digital Knowledge Management - Rianto, Toha; Nugroho, Arissetyanto; Zulkifli (International Journal of Science and Society, 2025)
This study examines the determinants of Organizational Performance in Small and Medium Industries (SMEs) of crafts by highlighting the role of Digital Knowledge Management (DKM) as the main mediator in the digital era. Using the Systematic Literature Review (SLR) approach referring to Kitchenham (2004) and PRISMA guidelines, 35 relevant articles were analyzed to identify key factors such as innovation, human resources, digitalization, and operational management that contribute to organizational performance. The findings show that DKM functions as a bridge connecting internal and external factors, strengthening organizational processes and driving long-term sustainability. This study also emphasizes the importance of digital knowledge management in supporting organizational adaptation to rapid changes in the business environment and increasingly fierce global competition. The practical implications of this study provide direction for SMEs to integrate DKM strategies into daily operations to improve effectiveness and competitiveness. These findings enrich the literature on knowledge management and Organizational Performance, especially in the context of developing countries. This study contributes to an in-depth understanding of the relationship between digital technology and business sustainability, opening up opportunities for the development of more adaptive and innovative policies and managerial practices.